GUIDELINES FOR BUILDING MORALE AND ENCOURAGEMENT IN THE PERFORMANCE OF TEACHERS FROM THE SITUATION OF THE OUTBREAK OF CORONAVIRUS DISEASE 2019 (COVID 19) IN THE MAE KHA SUBDISTRICT EDUCATIONAL QUALITY DEVELOPMENT CENTER UNDER THE JURISDICTION OF THE CHIANG MAI PRIMARY EDUCATIONAL SERVICE AREA OFFICE, AREA 3 - Supha, Weraphan; Kittirachadanon, Supaporn; Saengseemok , Suraphong (Journal of MCU Nakhondhat, 2024)
This research The objectives are 1) To study the problem of building morale and morale in teachers’ work. From the situation of the outbreak of coronavirus disease 2019 2) To find ways to build teachers’ morale and encouragement in their work. From the situation of the spread of coronavirus disease 2019. This research study uses a mixed methods research method. The research is divided into 2 stages: the stage is to study the conditions and problems of building morale and morale in the work of teachers from the situation of the outbreak of coronavirus disease 2019. and finding ways to build teachers’ morale and encouragement in their work. From the situation of the outbreak of coronavirus disease 2019, the target group Including 80 teachers in the Mae Kha Subdistrict Educational Quality Development Center, academic year 2023. The informants were 9 experts. Data were collected using questionnaires and structured interviews. Data were analyzed by finding frequencies, percentages, and standard deviations. and content analysis The research results found that 1) Conditions for building teachers’ morale and encouragement in their work. It was found that overall and each aspect It is at a high level ( = 4.22, = 0.63). When considering each aspect, arranging the average from highest to lowest, that is, job satisfaction has an average level of high. Next is the aspect of leadership or command. Relationship with leaders or supervisors and working environment, respectively 2) Guidelines for developing teachers’ morale and encouragement in their work. It was found that the leadership aspect or supervisors, that is, educational institutions should assign duties that match their abilities Regarding job satisfaction, educational institutions should provide teachers with financial planning training. Working environment That is, educational institutions should evaluate the environment. The relationship with leaders or supervisors is Educational institutions should exchange attitudes together.